2008
DOI: 10.1063/1.2829807
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the transient formation of molecular hydrogen on the microcrack nucleation and evolution in H-implanted Si (001)

Abstract: We study the implant-induced hydrogenated defects responsible for the Smart Cut™ layer transfer of Si ͑001͒ films. Different experimental methods are used to quantify the time dependence of the defect evolution and interactions during isothermal annealings. An optical characterization technique was developed for the statistical analysis of the formation and growth of micrometer size microcracks in the buried implanted layer. We show that the formation of molecular hydrogen is dominated by a transient phenomeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 20 publications
(27 reference statements)
2
58
0
Order By: Relevance
“…Platelet nucleation and growth occur through the coprecipitation of gas atoms ͑H and/or He͒ and vacancies. 11,15 Our TEM and SIMS results show that the behavior of H is quite similar in H-only implanted Si and SiGe samples after annealing at moderate temperature, although some small differences in binding energies exist. We do not expect that He behaves radically differently in SiGe than in Si.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Platelet nucleation and growth occur through the coprecipitation of gas atoms ͑H and/or He͒ and vacancies. 11,15 Our TEM and SIMS results show that the behavior of H is quite similar in H-only implanted Si and SiGe samples after annealing at moderate temperature, although some small differences in binding energies exist. We do not expect that He behaves radically differently in SiGe than in Si.…”
Section: Discussionmentioning
confidence: 86%
“…9,11 Figure 4 shows the SIMS profiles of H and He obtained after sequential implantations in Si ͓Fig. 4͑a͔͒ and SiGe ͓Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the thermal annealing temperature increases, the hydrogen filled microcavities keep growing. 24,25 Subsequent annealing and a combination of the buildup of internal gas pressure in the cavities and the growth of the micro-cavities leads to layer splitting by micro-crack propagation. Moutanabbir et al, (2010a) 26 concluded that thermoevolution of defects in H implanted and annealed freestanding GaN under ion-cut conditions revealed nanobubbles of 1-2 nm in diameter formation around the damage band.…”
Section: Resultsmentioning
confidence: 99%
“…On this surface, the cylinder pennyshape microcracks are circles. The number of circles on the surface, as well as their diameter (average of 8 nm), has been chosen according to the experimental observations of Personnic et al [18]. Fig.…”
Section: Elements Of the Modelingmentioning
confidence: 99%